2015
DOI: 10.1097/cmr.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

A lineage-specific methylation pattern controls the transcription of the polycistronic mRNA coding MELOE melanoma antigens

Abstract: We recently characterized two melanoma antigens MELOE-1 and MELOE-2 derived from a polycistronic RNA overexpressed in the melanocytic lineage. This transcription profile was because of hypomethylation of the meloe proximal promoter in melanomas and melanocytes. Here, we investigate whether this demethylation was restricted to the meloe promoter or was linked to a general lack of methylation at the meloe locus in the melanocytic lineage. We establish the methylation pattern of the locus spanning more than 40 kb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This RNA probably belongs to the family of long intronic non coding RNA (lncRNA) [ 4 ] since it shares many of their features: it is located in the intron of HDAC4 in antisense direction, it is capped and polyadenylated and contains no long ORF but multiple short ORFs (< 100 aa) and is transcribed in a tissue specific manner i.e. the melanocytic lineage [ 5 , 6 ]. Despite their denomination as « non coding » RNAs, it was shown that many lncRNAs can in fact be translated into short polypeptides [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This RNA probably belongs to the family of long intronic non coding RNA (lncRNA) [ 4 ] since it shares many of their features: it is located in the intron of HDAC4 in antisense direction, it is capped and polyadenylated and contains no long ORF but multiple short ORFs (< 100 aa) and is transcribed in a tissue specific manner i.e. the melanocytic lineage [ 5 , 6 ]. Despite their denomination as « non coding » RNAs, it was shown that many lncRNAs can in fact be translated into short polypeptides [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic dysregulation of the cancer genome leads to the expression of genomic regions that are generally silent ( 51 ). For example, it was shown that the promoter of the polycistronic transcript meloe, which encodes the MELOE-1 and MELOE-2 cancer-specific peptides, is hypomethylated in melanoma ( 52 ). HERV sequences cover about 8% of the genome and can become reactivated in cancer ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic dysregulation of the cancer genome leads to the expression of genomic regions that are generally silent 53 . For example, it was shown that the promoter of the polycistronic transcript meloe, which encodes the MELOE-1 and MELOE-2 cancer-specific peptides, is hypomethylated in melanoma 54 . HERV sequences cover about 8% of the genome and can become reactivated in cancer 55 .…”
Section: Discussionmentioning
confidence: 99%